3D printing driving innovations in extreme low-temperature energy storage - Shutong Qin; Jiao Dai; Haoran Tian; Hanyuan Zhang; Jingru Huang; Tianqi Guan; Weilin Xu; Jun Wan (Virtual and Physical Prototyping)
Extreme low-temperature environments, such as those in aerospace, polar expeditions, and deep-sea exploration, demand efficient energy storage systems. Conventional technologies face major limitations under these conditions, including electrolyte freezing, restricted interfacial reaction kinetics, and microstructural instability. In contrast, 3D printing offers transformative solutions with precise microstructural control, multifunctional material integration, and interfacial optimisation, effectively addressing challenges related to material compatibility and structural complexity. However, the mechanisms for optimising low-temperature material performance remain poorly understood, and the compatibility of 3D printing processes with such materials needs further exploration. Moreover, comprehensive integration of materials, processes, and device designs remains an ongoing challenge. This review systematically summarises key materials and their microstructural characteristics for low-temperature energy storage, exploring the potential mechanisms and pathways through which 3D printing enhances performance. Particular emphasis is placed on its unique applications in structural design, interfacial engineering, and multi-material coupling. Unlike studies focused on single materials or technologies, this review adopts an interdisciplinary and systematic framework, linking material properties with 3D printing optimisation. It provides critical theoretical guidance and practical insights for advancing the scientific understanding and engineering applications of extreme low-temperature energy storage technologies.This review explores 3D printing technologies as a transformative approach, integrating material design and advanced manufacturing to address structural optimisation and interfacial engineering challenges in extreme low-temperature energy storage.